Pengembangan Media Vidio Berbantuan Boneka Tangan Untuk Membina Karakter Anak Usia Dini di Tk Pkk Kartini Kota Batu - Fitriyah, Ida Afifa; Akbar, Sa'dun; Sobri, Ahmad Yusuf (Universitas Nahdlatul Ulama Blitar, 2025)
The development of hand-puppet-assisted video media to foster character education in early childhood is an effective approach within visual communication design to support learning activities. This media aims to help young children understand character values through engaging and developmentally appropriate visual content. It also serves as a learning aid for educators and parents in applying strategies that can enhance children’s motivation and participation. This study was conducted at Kartini Kindergarten in Batu City and focused on describing a learning model that utilizes hand-puppet-assisted video media for early childhood character development. The research employed a Research and Development (R&D) method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. Data were collected through questionnaires and literature reviews and analyzed using an interactive data analysis model. The results show that the media is feasible based on expert validation and received positive responses from teachers and children. The media also increased children’s engagement and positive behavior during learning activities, indicating its effectiveness as an innovative learning medium for early childhood education.